Pengaruh Persepsi Risiko Terhadap Keputusan Investasi Dengan Motivasi Investasi Sebagai Variabel Mediasi Pada Generasi Z Di Kota Makassar - Andi Fani Amalia; Rika Dwi Ayu Parmitasari; Eka Indriyani (Yayasan pendidikan dzurriyatul Quran, 2026)
The increasing number of young investors in Indonesia shows that investment decisions are becoming increasingly important for Generation Z in managing finances and planning for the future. This study aims to find out and explain the influence of risk perception on investment decisions with investment motivation as a mediating variable in generation Z in Makassar City. This study is included in quantitative research with a non-probability sampling method with a sample extraction technique using purposive sampling and a sample of 140 respondents. The analysis tool uses SmartPLS 4.1.17 using the SEM-PLS method. Based on the data analysis carried out, the results were obtained that all the hypotheses submitted were proven to have a positive and significant effect, namely, risk perception has a positive and significant effect on investment decisions in generation Z in Makassar City. Risk perception has a positive and significant effect on investment motivation in Generation Z in Makassar City. Investment motivation has a positive and significant effect on investment decisions in Generation Z in Makassar City. Risk perception indirectly has a positive and significant effect on investment decisions through investment motivation in generation Z in Makassar City. The implications of this study show that having a good understanding of risk perception can increase motivation for Generation Z to make investments and help them make more rational and structured investment decisions.